Pengaruh Model Pembelajaran Self Directed Learning (SDL) terhadap Kemampuan MenulisTeks Anekdot Siswa Kelas X SMK Negeri 1 Lubuk Pakam - Putri Suci Ramadhani; Susy Deliani Deliani; Sri Muliatik (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This study aims to determine the significant effect of the use of the Self Directed LearningModel on the ability to write anecdotal texts of class X students of SMK Negeri 1 LubukPakam.Thetypeofresearchusedisquantitativeresearchwithatwogrouppretest-posttestdesign. The population in this study were 68 class X students of SMK Negeri 1 LubukPakam. The instrument in this study the researcher used a test. Based on the results of thestudy, the ability to write anecdotal texts before using the Self Directed Learning learningmodelobtainedanaverageof55andastandard deviationof12.90994withadistributionof pre-test data tendencies included in the poor category. The ability to write anecdotaltexts after using the Self Directed Learning learning model averaged 83.1 and a standarddeviation of 7.021396 with a distribution of post-test data tendencies included in the verygoodcategory.Basedontheresultsofthehypothesistesting,tcountttable(10.8282.03452)wasobtained.ThismeansthatHoisrejectedandHaisaccepted,whichmeansthatthereisaninfluenceoftheSelfDirectedLearninglearningmodelontheabilitytowriteanecdotaltextsinclassXstudentsofSMKNegeri1LubukPakam.